UNPACKING THE INFLUENCE OF TRAVELOKA REVIEWS ON CONSUMER ACCOMMODATION CHOICES: HOW ONLINE FEEDBACK SHAPES TRAVEL DECISIONS - Stephanie, Angelina; Tan, Catherine Ardelia; Putridita, Vicka; Juliana, Juliana; Pramezwary, Amelda; Djakasaputra, Arifin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
In the digital era, online reviews have become pivotal in consumer decision-making, particularly in tourism and hospitality. This study examines the influence of online reviews on Traveloka, a leading online travel platform, in shaping consumer choices for accommodation. By analyzing user-generated content, ratings, and comments, this research aims to understand how review credibility, rating scores, and reviewer expertise impact consumers' trust and final booking. The target population for this study comprises individuals who have booked accommodations through Traveloka within the past year. A purposive sampling method ensures the respondents have relevant and direct experience with the platform. Based on the Krejcie-Morgan table for determining sample sizes, a target of 100 respondents is set to ensure the results are statistically significant, and generalizable findings reveal that high ratings, detailed feedback, and verified reviews significantly influence consumer trust, leading to a higher likelihood of booking. Moreover, the study highlights that negative reviews, while potentially deterring, also play a role in establishing the authenticity of positive feedback, thereby strengthening overall consumer confidence. This research underscores the importance of managing online reviews and provides valuable insights for hospitality businesses aiming to enhance their reputation and attract potential customers through effective review management.